Analyzing the drivers of sustainable value creation, partnership strategies, and their impact on business competitive advantages of small & medium enterprises: a PLS-model - Hariastuti, Ni Luh Putu; Pratikto, Pratikto; Santoso, Purnomo Budi; Tama, Ishardita Pambudi (Eastern-European Journal of Enterprise Technologies, 2021)
Sustainable manufacturing is a critical phenomenon in the process of creating sustainable value. This is a way to increase innovation and resource quality. On the other hand, the partnership strategy is an important factor in efforts to improve company performance. The involvement of the partnership strategy is one of the factors that strengthen the achievement of sustainable values. Furthermore, this affects the sustainability of a manufacturing company's competitiveness, including Small and Medium Enterprises (SMEs). In this study, we focus on creating sustainable value and the role of partnership strategies in improving the business performance of SMEs engaged in the metal manufacturing industry. The Partial Least Squares (PLS) approach to Structural Equation Modeling (SEM) is used to evaluate relationships and effects based on survey data from small and medium industries. The results show that the creation of sustainable value, including products, processes, production, equipment, organization, and human values, has a significant impact (β=0.522; ρ<0.001) on increasing the competitiveness of small and medium enterprises. The effect of sustainable value creation on sustainable competitiveness is fully moderated by the partnership strategy (β=0.179; ρ=0.03), especially in the technology & equipment, and human resources. Apart from being a moderating variable, the partnership strategy has also been shown to significantly act as a partial mediating variable (β=0.135; ρ<0.05) for sustainable value creation in enhancing competitiveness. The partnership strategy's simultaneous involvement proves that the partnership strategy plays an important role in value creation to increase the competitiveness of sustainable manufacturing SMEs